The Effect of Pressure, Opportunity, Rationalization, Gender, and Workload on The Action of Fraud - Murdianingrum, Sri Luna; Widiastuti, Sri Wahyuni (RSF Conference Series: Business, Management and Social Sciences, 2021)
This research aims to test the effect of financial pressure, opportunity, rationalization (fraud triangle), gender, and workload on the action of fraud. The data used in this research is the primary data using questionnaires that were distributed to 60 respondents with the technique of sampling slovin. The respondent of this research is an academic community of regional work unit of Department of Accounting, Faculty of Economics and Business, Yogyakarta "Veteran" National Development University. This research using quantitive methods such as multiple linear regression analysis. This research found that the action of fraud is not affected by pressure, opportunity, rationalization, gender, and workload.